Genomes of Helicobacter pylori prophages - Vale, F.F. (2016)
Nearly 20% of the Helicobacter pylori genomes carry prophages genes. Recently we were able to clearly differentiate four populations of prophages according to geographical origin of host strain. Interestingly we were able to discriminate between Northern Europe and Southern Europe using a phage sequence typing based on 2 prophage genes of H. pylori (integrase and holin) but present in only a minority of strains.